2009
DOI: 10.1007/s00535-009-0111-1
|View full text |Cite
|
Sign up to set email alerts
|

The synthesized 2-(2-fluorophenyl)-6,7-methylenedioxyquinolin-4-one (CHM-1) promoted G2/M arrest through inhibition of CDK1 and induced apoptosis through the mitochondrial-dependent pathway in CT-26 murine colorectal adenocarcinoma cells

Abstract: Taken together, CHM-1 acted against colorectal adenocarcinoma cells in vitro via G2/M arrest and apoptosis, and CHM-1-P inhibited tumor growth in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 20 publications
3
23
0
Order By: Relevance
“…Cytochrome C is released from the intermembrane space of mitochondria into the cytosol and activates the caspase-9 proenzyme, which, in turn, activates caspase-3, which cleaves PARP to initiate a caspase cascade leading to apoptosis. 29,50 Our results were in agreement with those of previous studies. We also observed that the translocation of BAX and cytochrome C might be because BAX proteins anchor to the mitochondria, whereas cytochrome C is released following SDT.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Cytochrome C is released from the intermembrane space of mitochondria into the cytosol and activates the caspase-9 proenzyme, which, in turn, activates caspase-3, which cleaves PARP to initiate a caspase cascade leading to apoptosis. 29,50 Our results were in agreement with those of previous studies. We also observed that the translocation of BAX and cytochrome C might be because BAX proteins anchor to the mitochondria, whereas cytochrome C is released following SDT.…”
supporting
confidence: 94%
“…Six hours after SDT, macrophages were loaded with 5 μM calcein-AM (GenMed Scientifics Inc., Wilmington, DE, USA) in the presence of 5 mM cobalt chloride in the dark for 20 minutes at 37°C as previously described. 29 The cells were carefully washed twice with PBS, and fluorescence was monitored via fluorescence microscopy. Calcein-AM fluorescence was measured at 525 nm following excitation at 488 nm.…”
Section: Measurement Of Changes In the Mptpmentioning
confidence: 99%
“…About 6 h after the PDT treatment, the cells were stained with 5 µM calcein AM (GenMed Scientifics Inc., Arlington, MA, USA) in the presence of 5 mM cobalt chloride in the dark for 20 minutes at 37°C, as previously described. 21 The cells were then carefully washed twice with PBS. Fluorescence was examined using a fluorescence microscope (Olympus IX81, Olympus Corporation), and the change in MPTP following the PDT treatment was also determined using the same method.…”
Section: Detection Of Mptp Changesmentioning
confidence: 99%
“…It was also reported that the G2/M checkpoint plays an important role for DNA damage-induced apoptosis. The CDK1/Cyclin B complex is the major regulator leading the G2 to M phase progression (2,9). Recently, it was reported that p21, a potent cyclin-dependent kinase inhibitor (CKI), is a key regulator, and it can inhibit the CDK1 activity and strengthen the G2/M arrest of cell cycle distribution (15,31).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of cell cycle arrest and apoptosis in tumor cells may be a considered strategy for colon cancer. The process of cell cycle has been investigated frequently, particularly CDK1/Cyclin B complex play an important role for regulation of G2/M phase (2,3). Much evidence shows that tumor cells can be induced to cell death through cell arrest and apoptosis (4,5).…”
Section: Introductionmentioning
confidence: 99%